Literatur Review: Hubungan Emosi dan Motivasi Terhadap Prestasi Olahraga Beladiri - Arina Nailul Wafiiroh; Ajeng Dian Purnamasari; Dyah Woro Dwi Lestari (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Sport is an intensive activity to foster and bring out the potential of athletes so that they get achievements, one of which is martial arts. Achievement must pay attention to four important factors, one of which is psychological factors, especially emotions and motivation. These psychological factors are still not considered by athletes and coaches. The existence of thetitles of articles and journals regarding the relationship of emotions and motivation to the achievement of martial arts encourages researchers to conduct a literature review study. The purpose of this study was to determine how big the relationship between emotion and achievement in martial arts, and motivation on achievement in martial arts. This research uses the Literature Study method. The literature data collection technique uses the PICOT (Population, Intervention and Comparation, Outcome, Time) method using the google scholar search engine and the garuda portal. The keywords used are emotion, motivation, achievement in martial arts. How to select the data in this study using the PRISMA method, written on the Literature Review flow diagram. Data analysis uses a thematic approach. Based on the inclusion and exclusion criteria, 7 journals were obtained with 4 journals discussing emotions and 3 journals discussing the relationship between motivation and achievement. The psychological aspect of emotion has a relationship with theachievement of martial arts by 77.8%, 42.6% and 78.6%. The psychological aspect of motivation has a relationship with the achievement of martial arts by 42.5%, 90.2% and 15%. Emotions have a greater relationship than motivation to martial arts achievement. There is a relationship between emotion and motivation on self-efficacy in sports. Emotions have a greater relationship than motivation to self-defense sports achievement.